Studies in church history - Parsons, Reuben (John Joseph McVey, 1886)
v. 1. Centuries I.-VIII.--v. 2. Centuries IX.-XIV.--v. 3. Centuries XV.-XVI.--v. 4. Centuries XVII.-XVIII.--v. 5. Century XIX. pt. I.--v. 6. Century XIX. pt. II.